Management of Patients with Textured Surface Breast Implants. Issue 4 (29th March 2021) - Savetsky, Ira L.; Gabriel, Allen; Rohrich, Rod J.; Avashia, Yash J.
Abstract : Summary: The purpose of this special topic article is to present an evidence-based approach and provide recommendations for the management of both asymptomatic and symptomatic patients with textured surface breast implants. There are currently no scientific data to support complete removal of a benign capsule. When unnecessary capsulectomies are performed, the patient is at higher risk for developing postoperative complications. Ultimately, the decision to keep, exchange, or remove breast implants is the patient's decision and the procedure should be performed only by a qualified surgeon.